2014
DOI: 10.1016/j.chom.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Lipopolysaccharide Binding Enhances Virion Stability and Promotes Environmental Fitness of an Enteric Virus

Abstract: Summary Enteric viruses, including poliovirus and reovirus, encounter a vast microbial community in the mammalian gastrointestinal tract, which has been shown to promote virus replication and pathogenesis. Investigating the underlying mechanisms, we find that poliovirus binds bacterial surface polysaccharides, which enhances virion stability and cell attachment by increasing binding to the viral receptor. Additionally, we identified a poliovirus mutant, VP1-T99K, with reduced lipopolysaccharide (LPS) binding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
373
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(395 citation statements)
references
References 42 publications
(55 reference statements)
16
373
6
Order By: Relevance
“…Alternatively, there could be a coreceptor for RV-C that interacts with CDHR3, or a cofactor that facilitates binding and entry. For example, bacterial surface polysaccharides stabilize polioviruses and facilitate cell attachment by increasing binding to the viral receptor (33,34). In any case, experiments in our laboratory and elsewhere demonstrated that the RV-C interaction with native HeLa cells or other cell lines (e.g., A549) is not sufficient for efficient virus entry and replication (5,6,35).…”
Section: Discussionmentioning
confidence: 94%
“…Alternatively, there could be a coreceptor for RV-C that interacts with CDHR3, or a cofactor that facilitates binding and entry. For example, bacterial surface polysaccharides stabilize polioviruses and facilitate cell attachment by increasing binding to the viral receptor (33,34). In any case, experiments in our laboratory and elsewhere demonstrated that the RV-C interaction with native HeLa cells or other cell lines (e.g., A549) is not sufficient for efficient virus entry and replication (5,6,35).…”
Section: Discussionmentioning
confidence: 94%
“…Depletion of commensal bacteria by antibiotics inhibits poliovirus replication and pathogenesis in mice [147], although this was not seen in human infants given therapeutic doses of azithromycin [28]. It has also been observed in vitro that poliovirus infectivity is enhanced by exposure to bacterial surface polysaccharides such as lipopolysaccharide and peptidoglycan [147], possibly via the effect of these polysaccharides on virion stability and receptor attachment [148]. Analogous effects have been reported for rotavirus, which exhibits reduced infectivity and pathogenicity (but greater immunogenicity) in antibiotic-treated mice [149].…”
mentioning
confidence: 98%
“…Although we do not yet know the precise mechanism by which a HBGA (either free or bacterial-bound) stimulates HuNoV infection of B cells, we determined that it facilitates viral binding to the surface of B cells. Based on a previous study showing that LPS stimulates poliovirus binding to its receptor on permissive cells, 44 we speculate that the HBGA plays a similar role in bridging NoV attachment to a yet-to-be-identified entry receptor expressed on B cells.…”
Section: Commensal Bacteria Facilitate Norovirus Infectionsmentioning
confidence: 99%